How long does it take to start minimal enteral feeding in preterm Neonates admitted to NICUs in Southern Oromia, Ethiopia? - Anteneh Fikrie; Terefu Yambo; Alo Edin; Miesa Gelchu; Dejene Hailu; Mark Spigt (Italian Journal of Pediatrics)
Abstract Background The timely initiation of trophic feeding (TF) is crucial for premature newborns, but challenging due to immaturity, respiratory instability, abdominal distension, resource scarcity, and healthcare worker expertise. Moreover, there is a dearth of information on predictors of full trophic feeding time. Therefore, this retrospective cohort study aimed to investigate the time it takes and its predictors to initiate minimal enteral feeding in preterm neonates in Southern Oromia, Ethiopia. Method A facility-based retrospective follow up study was conducted among 434 randomly selected preterm neonates admitted to NICU of Bule Hora University Teaching Hospital and Yabello General Hospital from January 1, 2021 to December 30, 2022. Data were extracted by a pretested structured checklist, entered into Epidata 3.1 and then transferred to Stata version 17 for analysis. Kaplan Meier survival curve and log rank test were used to estimate survival time and a statistical comparison respectively. Bivariable and multivariable cox proportional hazard model was fitted to identify predictors of time to initiate TF and their outputs are presented using Adjusted Hazard Ratio (AHR) with 95% Confidence Intervals (CIs). Result The overall incidence density of TF initiation was reported as 43.6 per 100 neonate-days. Moreover, the median (IQR) time to initiate TF was found to be 2 (1–4) days. Neonates delivered vaginally had a higher likelihood of early TF initiation (AHR: 1.64, CI: 1.26, 2.13), while those born between 32 and 34 weeks (AHR: 0.61, CI: 0.46, 0.81), VLBW neonates (AHR: 0.45, CI: 0.34, 0.60), neonates without KMC (AHR: 0.59, CI: 0.46, 0.79), and those in level II hospitals were less likely to start TF promptly (AHR: 0.78, CI: 0.62, 0.99). Furthermore, neonates with sepsis (AHR: 1.76, CI: 1.36, 2.28) and hypothermia (AHR: 1.51, CI: 1.19, 1.93) had delayed TF initiation. Conclusion We observed a significant low rate of early TF initiation and higher death rate of preterm newborn in our study as compared to the global. Preterm neonates with lower GA, no KMC, and a VLBW are more likely to have a delayed initiation. Our results highlight that staff training on identifying neonates suitable for TF, and ensuring adequate resources for KMC in all NICU levels should be considered.